Effects of cocktail enzymes supplementation on performance and gut morphology of arbor-acre broilers fed low density diets based on corn-soyabean meal (2014)
The effect of maxigrain cocktail enzyme on performance and gut morphology were investigated in a 42-day feeding trial. A total of 240 one-week-old arbor-acre broiler chickens were fed the following diets at the finisher phase: Treatment 1 (T1): 21% CP+3000 kcal/kgME-Enzyme, Treatment 2 (T2): 21% CP+3000 kcal/kgME+Enzyme, Treatment 3 (T3): 21% CP+2600 kcal/kgME-Enzyme, Treatment 4 (T4): 21% CP+2600 kcal/kgME+Enzyme, Treatment 5 (T5): 17% CP+3000 kcal/kgME-Enzyme, Treatment 6 (T6): 17% CP+3000 kcal/kgME+Enzyme. The experimental design was a completely randomized design. The birds were randomly assigned to six (6) dietary treatments of 4 replicates each and 10 birds per replicate. The birds were fed ad-libitum and were weighed on a weekly basis to determine their growth performance. On day 42, four birds were slaughtered and sections of the duodenum, ileum and jejunum (1 cm) were removed for gut histomorphology. Maxigrain enzyme supplementation significantly increased the performance (average body weight again (ABWG), total average feed intake (TAFI)) especially with birds on treatment 1 (T1) and treatment 2 (T2). Although, birds fed treatments 4 (T4) compared favourably with those on treatment 1 (T1). Enzyme supplementation had significant (P<0.05) effect on the villus height (VH), crypt depth (CD), villus width (VD), muscular width (WD) and the villus to crypt depth ratio (V:CD) of the birds duodenum, jejunum and ileum sections across the treatments. These dietary supplement had significant (P<0.05) effect on the villus height (1629.00 µm-5620.00 µm (duodenum), 1731 µm-6851 µm (jejunum), 1149 µm-5061 µm (ileum)), crypt depth (155.00 µm-641.10 µm (duodenum), 214.40 µm-873.60 µm (jejunum), 158.60 µm-751.10 µm (ileum)), villus width (148.40 µm-426.30 µm (duodenum), 151.00 µm-538.10 µm (jejunum), 131.60 µm-675.50 µm (ileum)) and muscular width (421.70 µm-1347.30 µm (duodenum), 445.30 µm-1347.30 µm (jejunum), 334.30 µm-1584.60 µm (ileum)) and the villus to crypt depth ratio (7.90-12.03 (duodenum), 7.84-9.83 (jejunum), 6.02-11.21 (ileum)). Effect of enzyme inclusion better increased the histomorphometric parameters measured of bird's duodenum, jejunum and ileum particularly of birds on T4. The villus to crypt depth ratio of bird's duodenum section fed T2 and T6 were increased by enzyme supplementation however, there were decreases in the jejunum and ileum sections of birds fed T2 and T4. Maxigrain cocktail enzyme resulted in improved growth performance and gut morphology of broiler birds fed low energy diets, giving a cost-effective nutritional strategy for profitable broiler production.